(untitled) - Ministry of Water Resources; Southern Institute of water Resources Research (Thành Phố Hồ Chí Minh, 1991)
Contents of volume 2: Containing 10 papers about: Approach for modelling basic processes in soils and propagation of acid water in canal system; Some experiences and methods of acid sulphate soils reclamation in the Plain of Reeds.
Keywords: Acid sulfate soils; Management,Simulation methods